Web Resources Development Methdology Based on Web Composition Using Ontology for User’s Optimal Goal - Narayanan, G; Periasamy, Pon (International Journal of Computer Sciences and Engineering, 2025)
The proposed algorithm expands the meaning of a user’s goal using ontology then derives a group of keywords to discover services and web composition are used to select the web services based on QoS to find the optimality solution of their user goal. The efficiency of the web service matching and composition becomes more important than ever because of the vast number of the web services. For this purpose we propose a web service composition algorithm based on the annotated ontology using semantic matching to achieve exact service for user’s constraint. We design a resource graph to represent the semantic relationship among Web resources. By analyzing the relations among Web resources and using ontologies, A semantic web services would require careful usage combined technologies this semantic web service is realized to show that they ensure interoperability. Four aspects of web services are presented 1) Standard of XML web services 2) Semantic annotation 3) Web service composition 4) Performance Evolution. Our framework can generate ad-hoc processes for composing Web resources. We have built a prototype to demonstrate that the repetitive tasks in the Web resources can be automatically and tracked and the user can change simple Web resources into reusable services by annotating the data with them.